2011
DOI: 10.1590/s0036-36342011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Cultura organizacional de enfermería dominante en un hospital de la Secretaría de Salud de Morelos, México

Abstract: Identifying said organizational culture models helps to understand performance differences in the management of nursing care services currently provided to users of the hospital and to aspire to improvements in the service itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The concept of organizational climate has been defined as “the atmosphere that employees perceive is created in their organization by (management) practices” [ 40 ]. Health workers’ desire for a more supportive organizational environment has been highlighted in previous studies, and the association between organizational climate and health workers’ satisfaction in their job have been documented previously in LMIC settings [ 20 , 31 , 37 , 41 ]. Focus on management of relationships and relationship building has been promoted as an approach to improving the quality of health care work environment, strengthening health workers’ perception of organizational support and their commitment to organizational goals [ 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…The concept of organizational climate has been defined as “the atmosphere that employees perceive is created in their organization by (management) practices” [ 40 ]. Health workers’ desire for a more supportive organizational environment has been highlighted in previous studies, and the association between organizational climate and health workers’ satisfaction in their job have been documented previously in LMIC settings [ 20 , 31 , 37 , 41 ]. Focus on management of relationships and relationship building has been promoted as an approach to improving the quality of health care work environment, strengthening health workers’ perception of organizational support and their commitment to organizational goals [ 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…Te concept of organizational commitment amongst nurses has been studied in various hospitals, with a focus on its impact on healthcare quality and patient safety. In Mexico, a study on the dominant culture amongst nurses in a public hospital revealed the need for consensus on values, attitudes, and behaviours to strengthen and develop hospital organizations [117]. In Catalunya, Spain, a study on nursing governance and its impact on perceived quality showed a positive correlation between patient satisfaction and safety with the work of nurses and their commitment to the organization [118].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Regardless of their general basis, the CVF-type subcultures have been widely used in studies of health organizations and professionals (Dimitrios et al, 2014;Villarreal et al, 2012;An et al, 2011;Singer et al, 2009). Another study with different types of MRJIAM 14,1 subcultures to those mentioned above was performed on nursing staff in Mexico by Ortega-Altamirano et al (2011), based on four options: power, function or task, performance and support, based on the autonomy granted to the groups of people in their activities.…”
Section: Subcultures In Homentioning
confidence: 99%